(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Dynamic of changes, transformation and permanency in environment of Pasar Baru Bandung from 1906 - 2019 Pasar Baru as one of the growth poles of the city center of Bandung, whose development has helped to shape the urban characteristics of the downtown area. This environment undergoes changes and transformation in pattern, type, and system which related to its physical environment, during the initial formation of the area until now. The purpose of this study is to describe the non-physical change, transformation, and permanency in the Pasar Baru Bandung environment which affect it characteristics. The study approach is synchronic-diachronic with descriptive qualitative methods using historical reading from 1906 to 2019 and tissue analysis in 2019. Research carried out around Pasar Baru Bandung, including Jalan Otto Iskandardinata, Jalan ABC, Jalan Pecinan Lama, Jalan Alkateri and small streets in between. The results of this study indicate that the change in system often occurs in the environment related to access, however, access does not have any significant transformation compared to the physical structure. The function in the environment tends to be permanent compared with the transformation in building and the mass density of the environment.